2010
DOI: 10.1007/s00421-010-1568-6
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of aerobic exercise on the blood pressure, oxidative stress and eNOS gene polymorphism in pre-hypertensive older people

Abstract: The polymorphisms of endothelial nitric oxide synthase (eNOS) are associated with reduced eNOS activity. Aerobic exercise training (AEX) may influence resting nitric oxide (NO) production, oxidative stress and blood pressure. The purpose of this study was to investigate the effect of AEX on the relationship among blood pressure, eNOS gene polymorphism and oxidative stress in pre-hypertensive older people. 118 pre-hypertensive subjects (59 ± 6 years) had blood samples collected after a 12 h overnight fast for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 58 publications
3
28
0
8
Order By: Relevance
“…These findings are in agreement with most studies that measured blood pressure subsequent to AEXT in individuals with relatively normal resting blood pressure levels. In studies on normotensive and/or prehypertensive populations, blood pressure did not significantly change following AEXT in most cases [36, 37]. Conversely, a review by Hagberg et al reported that blood pressure significantly decreased in 75% of the hypertensive subjects following AEXT [38].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in agreement with most studies that measured blood pressure subsequent to AEXT in individuals with relatively normal resting blood pressure levels. In studies on normotensive and/or prehypertensive populations, blood pressure did not significantly change following AEXT in most cases [36, 37]. Conversely, a review by Hagberg et al reported that blood pressure significantly decreased in 75% of the hypertensive subjects following AEXT [38].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Zharikov et al [7] showed that almost 80% of patients with pulmonary hypertension had hyperuricemia. However, regular physical exercise has been considered the major stimulus to prevent and/or control high BP [8,9]. Briefly, physical exercise promotes an improvement in metabolic syndrome [10], autonomic modulation (heart-rate variability) [11], nitric oxide concentration and oxidative stress [4,9], lipid profile [12] and other disorders.…”
Section: Introductionmentioning
confidence: 99%
“…However, regular physical exercise has been considered the major stimulus to prevent and/or control high BP [8,9]. Briefly, physical exercise promotes an improvement in metabolic syndrome [10], autonomic modulation (heart-rate variability) [11], nitric oxide concentration and oxidative stress [4,9], lipid profile [12] and other disorders. Nevertheless, the effectiveness of regular exercise on UA content and its relationship with hypertension is still controversial, mainly because of the differences among type, intensity, frequency and duration of the exercise programs found in the literature [13-15], especially those related to elderly [5,14,16].…”
Section: Introductionmentioning
confidence: 99%
“…Given the potential role of nitric oxide in regulating tolerance to physical exercise and recovery mechanisms, these NOS3 genetic variants have been tested and/or associated with various training or exercise response phenotypes, such as: cardiovascular hemodynamics traits, e.g. blood pressure [21,22] and heart rate responses [23]; cardio-biochemical parameters [24]; adaptation to parasympathic modulation and the level of oxidative stress induced by aerobic exercise training [21,25]; vascular reactivity [26,27], and exercise-induced adaptation to hypoxia [28].…”
Section: Introductionmentioning
confidence: 99%